The responsibility to protect in Libya and Syria : mass atrocities, human protection, and international law - Nahlawi, Yasmine (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book offers a novel and contemporary examination of the 'responsibility to protect' (R2P) doctrine from an international legal perspective and analyses how the doctrine was applied within the Libyan and Syrian conflicts as two recent and highly significant R2P cases. The book dissects each of R2P's three component pillars to examine their international legal underpinnings, drawing upon diverse legal frameworks - including the laws of the UN, laws of international organisations, human rights law, humanitarian law, criminal law, environmental law, and laws of State responsibility - to extract conclusions regarding existing and emerging host and third-State obligations to prevent and react to mass atrocity crimes. It uses this legal grounding to critically examine specific aspects of the Libyan and Syrian R2P cases, engaging with some of the more traditional debates surrounding R2P's application, most notably those that pertain to the use of force (or lack thereof), but also exploring some of the less-researched non-military methods that were or could have been employed by States and international organisations to uphold the doctrine. Such an analysis captures the diversity in the means and actors through which R2P can be implemented and allows for the extraction of more nuanced conclusions regarding the doctrine's strengths and limitations, gaps in enforceability, levels of State support, and future trajectory. The book will be of interest to scholars and students in the field of international law and human rights law"--
Contextualising the Emergence of the Responsibility to Protect -- R2P's Pillar 1 -- R2P's Pillar 2 -- R2P's Pillar 3 -- The Application of R2P to the Libya Case -- The Application of R2P to the Syria Case.
Based on author's thesis (doctoral - Newcastle University, 2016) issued under title: The Responsibility to Protect : An Examination of Host and Third-State Obligations in Preventing and Reacting to Mass Atrocity Crimes in Light of the Libyan and Syrian Conflicts.
Includes bibliographical references (pages 183-193) and index.
Keywords: Responsibility to protect (International law); Syria -- History -- Civil War, 2011- -- Law and legislation; Libya -- History -- Civil War, 2011- -- Law and legislation